Penilaian Risiko Kebakaran dan Evaluasi Penerapan Alat Pemadam Api Ringan Pada Temporary Building Perusahaan Jasa Kontruksi - Vida Fadhilatu Rohma; Moch. Luqman Ashari (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
Temporary bulding or temporary buildings are places that have high urgency in a construction project where there are company facilities consisting of employees, buildings and company administration. This research is qualitative in nature, based on safety representative as the primary research data prior to conducting the Fire Risk Assessment which focuses on all rooms in the temporary buildings of construction service companies. This research was conducted with the aim of conducting a fire risk assessment in accordance with NFPA 551 of 2019 to determine the value of fire risk and Fire Extinguishers planning will be carried out based on Permenakertrans No. 04 of 1980. The results of the risk assessment carried out showed that the fire rate in 12 rooms in the temporary building had a moderate risk level and the other 2 rooms had a low risk level. For the application of Fire Extinguishers to the entire temporary building area, 5 Fire Extinguishers are needed with 4 Fire Extinguishers of the Dry Chemical Powder type and 1 Carbon Dioxide (CO2)